A discourse analysis of e-mail messages in a Malaysian Business Community - Ng, Yong Kiang (Penerbit UKM, 2003)
The study attempts to investigate recurrent grammatical features and functions of electronic mail discourse in a selected business community, comprising executives in a Malaysian public limited company. It also examines whether the electronic mail system has influenced language forms in the executives' e-mail discourse. Differences between language in the e-mail discourse and language in conventional business writing are explored too. The corpus comprises 102 electronic mail messages from the executives' routine communication in work contexts. The study examines grammatical features, communicative functions and discourse features of the messages. Findings reveal a predominance of main clauses in imperative and declarative moods, and subordinate clauses denoting purpose and reason, reflecting that e-mail communication of the community is used more for requesting and informing, and less for enquiring. Other discourse features like opening salutation, opening statement, closing statement and closing salutation are also found in the e-mail messages although they are not compulsory for such a communication. It is hoped that the language features and functions, and other discourse features identified in the e-mail communication of the business community would contribute towards pedagogy and course design for English for Business Communication, as well as for e-mail communication at the workplace .